Are atrophic long-bone nonunions associated with low-grade infections? - Dapunt U; Spranger O; Gantz S; Burckhardt I; Zimmermann S; Schmidmaier G; Moghaddam A (Dove Medical Press, 2015)
Ulrike Dapunt,1 Ole Spranger,2 Simone Gantz,1 Irene Burckhardt,3 Stefan Zimmermann,3 Gerhard Schmidmaier,2 Arash Moghaddam2 1Center for Orthopedics, Trauma Surgery and Spinal Cord Injury, 2HTRG–Heidelberg Trauma Research Group, Trauma and Reconstructive Surgery, Center for Orthopedics, Trauma Surgery and Spinal Cord Injury, Heidelberg University Hospital, 3Department for Infectious Diseases, Medical Microbiology and Hygiene, Heidelberg, Germany Abstract: Impaired fracture healing, especially when associated with bacterial infection, is a severe complication following long-bone fractures and requires special treatment. Because standard diagnostic techniques might provide falsely negative results, we evaluated the sonication method for detection of bacteria on implants of patients with fracture nonunions. A total of 49 patients with a nonunion (group NU) and, for comparison, 45 patients who had undergone routine removal of osteosynthetic material (group OM), were included in the study. Five different diagnostic methods (culture of tissue samples, culture of intraoperative swabs, histopathology of tissue samples, culture of sonication fluid, and 16S ribosomal DNA polymerase chain reaction of sonication fluid) were compared and related to clinical data. Among the diagnostic tests, culture of sonication fluid demonstrated by far the highest detection rate of bacteria (57%) in group NU, and rather unexpectedly 40% in group OM. Culture of sonication samples also revealed a broad spectrum of bacteria, in particular Propionibacterium spp. In conclusion, our results indicate that more bacteria can be detected on implants of patients with atrophic nonunions of long-bone fractures by means of the sonication procedure, which provides a valuable additional diagnostic tool to decide on a surgical procedure (eg, two-step procedure) and to further specify antimicrobial therapy. Keywords: sonication, osteosynthetic material, osteomyelitis